PELAKSANAAN KELOMPOK DUKUNGAN SEBAYA PADA WARGA BINAAN PEMASYARAKATAN DENGAN HUMAN IMMUNODEFICIENCY VIRUS DI LEMBAGA PEMASYARAKATAN JAWA TENGAH - Raswandaru, Marsela Riska; Andriany , Megah; Setiawati Dewi , Nur (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
HIV problems in prisons can continue to grow due to various factors such as individual and environmental factors. Correctional nurses as health workers contribute to health care practices, one of which is HIV/AIDS control by carrying out PSG for prisoners with HIV. So far PSG activities have only been carried out with unclear main tasks and functions, monitoring and evaluation that have not been equal between correctional institutions. This study aims to explore the implementation of PSG for inmates with HIV by correctional nurses in Central Java. This research was conducted using qualitative methods in seven correctional areas. The criteria for participants are correctional nurses, prisoners with HIV, NGOs who have carried out peer support group (PSG) activities. The number of participants until the data saturation occurred was seven correctional nurses, five prisoners with HIV, three NGOs. Data collection techniques with semi-structured interviews. Data analysis was performed using content analysis. Researchers get five themes. First, the role of the nurse as a counselor and facilitator. Second, PSG is carried out routinely and flexibly, but monotonously. Third, PSG was influenced by the interest of prisoners with HIV to disclose their status. Fourth, HIV status has not been disclosed, limited resources, and the movement of prisoners with HIV is an obstacle for PSG. Fifth, obstacles are overcome by approaching prisoners with HIV, leaders, and stakeholders. The conclusion from the research results is that the implementation of PSG for inmates with HIV by correctional nurses provides a very interesting picture. The theme obtained needs to get the attention of all parties to maintain the quality of care services and correctional nurses in carrying out PSG for prisoners with HIV.